Image processing based automatic recognition of asphalt pavement patch using a metaheuristic optimized machine learning approach. (April 2019) - Hoang, Nhat-Duc
Graphical abstract: Highlights: An automatic method for pavement patch detection is proposed. Image processing is used to compute pavement image texture. Least Squares Support Vector Machine is used for data classification. Differential Flower Pollination is employed for model optimization. The new model can achieve a good prediction result (CAR = 95%). Abstract: Patch detection is an important task in pavement condition survey. This study establishes an automatic approach for asphalt pavement patch recognition based on image texture analysis and hybrid machine learning algorithms. Features based on image texture that employs statistical properties of color channels and the gray-scale co-occurrence matrix are used by the Least Squares Support Vector Machine (LSSVM) for discriminating patched areas from non-patch ones. In addition, to optimize the LSSVM training phase, the Differential Flower Pollination (DFP) metaheuristic is used. A data set constructed from a set of 1000 image samples has been utilized to train and verify the proposed integration of image texture analysis techniques, LSSVM, and DFP. Experimental results show that the new model can achieve a good prediction result with Classification Accuracy Rate = 95.30%, Positive Predictive Value = 0.96, and the Negative Predictive Value = 0.95. Additionally, a patch detection program has been developed and compiled in Visual C# .NET to ease the implementation of the hybrid model. Thus, the newly developed method can be a potential tool for traffic management agencies during the phase of pavement condition evaluation.